Youth Work in Schools: Pathways to Sustainability, Well-Being and Democratic Communities - Stelios Pantazidis; Yannis Pechtelidis (Youth, 2025)
This study investigates the integration of youth work into school environments as a response to contemporary educational challenges. Drawing on the implementation of selected best practices in four European countries—Greece, Finland, Estonia, and Portugal—within the framework of the Youth Work in Schools (YWIS) Erasmus+ project, this research explores the potential of youth work to enhance school communities, promote sustainability, support student well-being, and deepen democratic practices. Employing a mixed-methods approach that combines case studies and survey data from educators and youth workers, the study examines the transformative impact of youth work in promoting inclusive, engaged, and resilient educational settings. Preliminary findings indicate that youth work contributes meaningfully to holistic youth development by creating collaborative school cultures, supporting emotional and social well-being, and encouraging active civic participation. Youth workers’ interventions—ranging from peer mentoring and participatory governance to sustainability initiatives—demonstrated the value of experiential, student-centred learning. However, the sustainable integration of youth work in education requires institutional openness, professional recognition, and systemic support. By analysing the reflections of practitioners across diverse national contexts, this paper offers critical insights for policymakers, educators, and practitioners aiming to bridge the gap between formal and non-formal education. It argues that embedding youth work in schools can serve as a catalyst for educational transformation, cultivating more democratic, sustainable, and supportive learning environments.